Environmental Outcomes of Urban Land System Change: Comparing Riparian Design Approaches in the Phoenix Metropolitan Area. (December 2020) - Stuhlmacher, Michelle; Andrade, Riley; Turner II, B.L.; Frazier, Amy; Li, Wenwen
Highlights: Divergent design intentions affect land system architecture (LSA). Certain LSA changes had outsized roles in shaping site differences. Overall, most design difference did not result in divergent environmental outcomes. Results provide insight on crafting urban riparian redevelopment goals. Abstract: In the face of climate change and other environmental challenges, an increasing number of cities are turning to land design to enhance urban sustainability. Land system architecture (LSA)—which examines the role of size, shape, distribution, and connectivity of land units in relation to the system's social-environmental dynamics—can be a useful perspective for examining how land contributes to the social and environmental aspects of urban sustainability. There are two gaps, however, that prevent LSA from fully contributing to urban sustainability dialogues. First, it is not well understood how urban design goals, as expressed by urban planners and other practitioners, relate to LSA and environmental outcomes. Second, most LSA work focuses on individual environmental outcomes, such as the urban heat island effect, instead of considering the broader suite of outcomes that LSA changes impact. Here, we undertake an integrated assessment of LSA impacts on surface urban heat island (based on land surface temperature), vegetation presence/health (based on NDVI), and bird biota at two riparian sites with different design intentions in the Phoenix, Arizona metropolitan area. The Rio Salado in Tempe underwent a city-led, infill redevelopment that mixed economic, recreational, and flood control design goals. The New River in Peoria experienced a more typical developer-driven urbanization. The contexts and design goals of the sites generated differences in their LSA, but only a few of these differences were sufficiently unique to contribute to divergent environmental outcomes. These differences reside in (1) the greater distribution of recreational land-covers and (2) increased surface water at the Rio Salado site compared to the New River site. Both changes are linked to land-cover patches becoming greener and cooler as well as a greater presence of waterbird and warbler species at the Rio Salado site. The distinctions between the sites provide insight for crafting design goals for redeveloping or restoring urban riparian landscapes in the Phoenix metropolitan area that are grounded in LSA. With the incorporation of additional relevant variables, especially socioeconomic ones, the research approach employed in this study provides a foundation for the assessment of other urban land system change.